2005
DOI: 10.1088/0268-1242/20/8/019
|View full text |Cite
|
Sign up to set email alerts
|

Organic light-emitting diodes with n-type silicon anode

Abstract: In an AlQ-based bilayer organic light-emitting diode, n-type silicon has been used as an anode, and semitransparent metals Sm (15 nm)/Au (15 nm) as a cathode. This device has much smaller currents at high voltages (>8 V) and a higher turn-on voltage than the device with an identical structure but an indium-tin oxide anode. By successively depositing ultra thin films of Au and AlQ on the n-Si surface, the device performances are improved significantly, reaching a power efficiency of 0.1 lm W −1 and a current ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The reports generally concluded that the performance of OLEDs with metal anodes is poorer than those OLEDs with ITO anodes. However, the metals of Au and Pt with proper surface treatment on non-ITO electrodes, such as Si and Al, have been reported to improve the performance of top emission OLEDs [19], [20] but no obvious studies on ITO electrodes for bottom emission OLEDs.…”
mentioning
confidence: 99%
“…The reports generally concluded that the performance of OLEDs with metal anodes is poorer than those OLEDs with ITO anodes. However, the metals of Au and Pt with proper surface treatment on non-ITO electrodes, such as Si and Al, have been reported to improve the performance of top emission OLEDs [19], [20] but no obvious studies on ITO electrodes for bottom emission OLEDs.…”
mentioning
confidence: 99%
“…Recently, there is a tendency to fabricate light-emitting devices from organic materials [1][2][3][4][5] compatible with silicon [6][7][8][9] to realize an efficient Si light source and hence the monolithic integration of electronics and photonics. 10) Such Si-based organic light-emitting devices (Si-OLEDs) can be made using simpler and cheaper techniques than those needed to create thin films of crystalline semiconductors on Si.…”
Section: Introductionmentioning
confidence: 99%
“…10) The reported Si-OLEDs usually comprise a combination of organic fluorescent materials with p-type Si; however, because of the limit of 25% quantum efficiency for fluorescent materials in the electroluminescence (EL) process and the overly strong hole injection ability of the bare ptype Si anode, the reported Si-OLEDs are so far not very efficient. [6][7][8][9] In this study, we combine organic phosphorescent materials [11][12][13][14] and the n þ -Si anode doped with Au to fabricate Si-OLEDs. Electrophosphorescent materials possess a theoretical 100% quantum efficiency; [11][12][13][14] Au-doped n þ -Si anode has an adjustable hole injection resulting in a much higher efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the perspective of the OLED industry, Si-based OLEDs also have an important application in the fields of, for example, microdisplay and active-matrix display. Owing to the relatively high work function, Si including n-Si had been considered a suitable anode candidate for OLEDs [1][2][3][4][5][6][7]. However, it has been shown that the use of bare p-Si as anode usually causes too much hole injection [6,7].…”
Section: Introductionmentioning
confidence: 99%